Effect of low‐level laser therapy on chemoradiotherapy‐induced oral mucositis and salivary inflammatory mediators in head and neck cancer patients. Issue 4 (30th March 2015) - Oton‐Leite, Angélica F.; Silva, Geisa Badauy L.; Morais, Marília O.; Silva, Tarcília A.; Leles, Cláudio R.; Valadares, Marize Campos; Pinezi, Juliana Castro D.; Batista, Aline C.; Mendonça, Elismauro F.
Abstract : Background and Objective: Oral mucositis (OM) is considered a painful and debilitating side effect in patients receiving head and neck cancer treatment. Low‐level laser therapy (LLLT) proved to be effective to prevent and treat chemoradiotherapy‐induced OM. The aim of this study was to evaluate the effect of LLLT in the severity of OM in patients with head and neck cancer and on the release of salivary inflammatory mediators. Clinical (score of OM severity) and biochemical parameters (concentration of inflammatory mediators, growth factors, and enzymes in saliva) were used. Materials and Methods: Thirty patients were randomized into two groups: control and laser. LLLT was performed three times a week in the laser group, while control group received sham irradiation. OM severity was assessed according to the World Health Organization (WHO) and National Cancer Institute (NCI) scales. Pro‐inflammatory and anti‐inflammatory cytokines (TNF‐α, IL‐6, IL‐1β, IL‐10, TGF‐β), growth factors (EGF, FGF, VEGF), and metalloproteinases (MMP2/TIMP2, MMP9/TIMP2) concentrations were assessed using ELISA test. Saliva samples were collected on admission, and at the 7th, 21st, and 35th sessions of radiotherapy. Results: The laser group showed a reduction in the severity of OM, which coursed with significantly diminished salivary concentration of EGF and VEGF in the 7th radiotherapy session and of IL‐6 and FGF in the 35th. There was a trend for reduced levels of IL‐1β, TNF‐α, IL‐10, TGF‐β, MMP2/TIMP2, MMP9/TIMP2 in the laser group compared to the control, however, no statistically significant differences were found. Conclusions: These findings demonstrated that LLLT was effective in reducing the severity of chemoradiotherapy‐induced OM and was associated with the reduction of inflammation and repair. Lasers Surg. Med. 47:296–305, 2015. © 2015 Wiley Periodicals, Inc.